1998
DOI: 10.1111/j.1532-5415.1998.tb06008.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Antioxidants and Cognitive Performance in Middle‐Aged and Older Adults: Results of the Austrian Stroke Prevention Study

Abstract: These observations are compatible with the view that some dietary antioxidants may protect against cognitive impairment in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 17 publications
6
55
0
1
Order By: Relevance
“…However, in a large multi-ethnic sample of elderly Americans poor memory performance was found to be significantly related (P = 0·025) only to serum levels of vitamin E, and not to levels of vitamins A and C, and Se and β-carotene (Perkins et al 1999). These results were obtained after statistical adjustment for confounding factors in the latter studies (Berr et al 1998;Perkins et al 1999), but this procedure was not done in the analysis of the SENECA data of Haller et al 1996(also, see Perrig et al 1997Schmidt et al 1998).…”
Section: Antioxidant Vitaminssupporting
confidence: 46%
“…However, in a large multi-ethnic sample of elderly Americans poor memory performance was found to be significantly related (P = 0·025) only to serum levels of vitamin E, and not to levels of vitamins A and C, and Se and β-carotene (Perkins et al 1999). These results were obtained after statistical adjustment for confounding factors in the latter studies (Berr et al 1998;Perkins et al 1999), but this procedure was not done in the analysis of the SENECA data of Haller et al 1996(also, see Perrig et al 1997Schmidt et al 1998).…”
Section: Antioxidant Vitaminssupporting
confidence: 46%
“…Several studies have compared non-demented adults and elderly subjects, dietary intake and plasma concentration of nutrients with cognitive status, the latter assessed by means of specific cognitive tests: Mini mental state examination (Folstein et al 1975), Mattis dementia rating scale (Mattis, 1976), Hodkinson abbreviated mental test (Gomez de Caso et al 1994). Several authors have come to the conclusion that micronutrients may protect against cognitive impairment in elderly people (Goodwin et al 1983;Gale et al 1996;Haller et al 1996;Schmidt et al 1998). Riggs et al (1996) have observed in healthy male subjects that both lower plasma concentrations of vitamin B 12 and folic acid and higher concentrations of homocysteine are associated with poorer spatial copying skills.…”
Section: Prophylaxismentioning
confidence: 99%
“…Vitamin E's protective effect against cognitive decline and neurodegenerative disease has been explored in several epidemiological and clinical studies during the last decade (125,126) . When plasma antioxidants and cognitive performance in middle-aged and older adults were measured in the Austrian Stroke Prevention Study, vitamin E was found to be significantly associated with cognitive functioning (127) . Rosenblum et al (128) reported a protective effect by vitamin E to ameliorate the adverse effects of endothelial cell injury from brain ischaemia.…”
Section: Antioxidant Vitamins E and Cmentioning
confidence: 99%